The dominance of the physicalist-reductionist approach to the study of consciousness and its evolution : the case for a non-physicalist paradigm : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Jackson, Peter Anthony (Massey University, 1992)
In this thesis it is argued that the dominant physicalist-reductionist view in psychology has hindered the study of consciousness and its evolution. The thesis begins with an overview of the physicalist-reductionist position, from a philosophical viewpoint. The weakness of this position is exposed in that matter can be viewed not as a physical substance, but as the derivative of a non-physical realm. This is argued by using the theory of David Bohm, who postulated the existence of an implicate order (hidden from the senses) and an explicate order (the sensory realm). Bohm's reasoning is explored and justified, where his theory is shown to be the way to reconciling the difficulties faced by quantum mechanics and relativity theory. Using Bohm's implicate-explicate notion as a basis, an implicate-explicate model of the evolution of consciousness is developed. This model is able to deal with biological evolutionary factors, and not simply with the evolution of consciousness. This is because the model assumes that biological forms evolved as a result of the interaction between the implicate and explicate orders. In this model, evolution is seen as the unfolding of what lies implicate, which then becomes explicate. The earliest stages of this unfolding were automatic, and led to increasingly complex physical, chemical, then biological structures. A stage was reached where biological structures gave rise to sufficiently complex neural structures which, in turn, permitted consciousness to appear. In this model, consciousness is a very high order explicate of a special region within the implicate order, which is called Mind. Thus, the evolution of consciousness is the result of the unfolding of Mind. The model shows that consciousness is an active factor in the further evolution of biological forms. The notion of consciousness is explored and a variety of theories of consciousness are reviewed and critiqued, where these are examined in the light of the implicate-explicate model. This model is then used to explore the way consciousness evolves through the infrahuman life forms to the human form. Palaeoanthropological evidence is used to justify the claim that consciousness has evolved, with a special focus on primate evolution, and on the critical phase of transition from proto-human to truly human consciousness. In this, the acquisition of speech is seen as crucial, where the implicate-explicate model offers an explanation for this acquisition. The notion of psychological paradigms is explored, and a set of paradigms delineated, where these are located along a spectrum of the relevance of consciousness to any given paradigm. The relevance spectrum is related to the implicate-explicate model as a metaparadigm. This is used to reveal the strengths and limitations of the various paradigms. The implicate-explicate model shows that present day humans have reached an impasse in the evolution of their consciousness. A means to overcoming this is suggested, and the next stage in the evolution of consciousness that might arise is speculated upon.
Keywords: Evolutionary psychology; Evolution; Consciousness